Developing teaching materials on elasticity and hooke's law oriented towards learner autonomy to train science process skills - Risda, Gusti; Arifuddin, Muhammad; Misbah, Misbah; Saukani, Muhammad (Journal of Environment and Sustainability Education, 2023)
Low science process skills contribute to a lack of learner autonomy among students. This research aims to develop teaching materials on elasticity and Hooke's law oriented towards learner autonomy to enhance science process skills suitable for the learning process. The study follows the ADDIE development model (analyze, design, develop, implement, and evaluate). The research subjects were 32 students from class XI MPA 1 at SMA Negeri 6 Banjarmasin. Data were collected through validation sheets, observation sheets on the implementation of lesson plans, observation sheets on science process skills, and learning outcome tests. Quantitative data analysis methods were employed. The results indicate that: 1) the teaching materials are highly valid according to validator assessments, 2) the materials are highly practical based on lesson plan implementation, 3) the effectiveness of the teaching materials is moderate, and 4) students' science process skills are categorized as good based on student activity sheets. In conclusion, learner-autonomy-oriented teaching materials are suitable for training science process skills in the topics of elasticity and Hooke's law.